Prevalence of non alcoholic fatty liver disease in systemic hypertension - DR. N. DEEPTHI; DR. E. DHANDAPANI (International Journal of Pharma and Bio Sciences, 2018)
Non alcoholic fatty liver disease (NAFLD) is the most common liver disease. It is now increasingly recognized as a major cause of liver-related morbidity and mortality. NAFLD is getting an increasing attention for its clinical implications on cardiovascular disease (CVD). NAFLD is considered a risk factor for hypertension. Few studies are reported stating the reverse causality, prevalence of NAFLD in hypertension. However, epidemiologic data are not so evident to sustain the causative association between NAFLD and hypertension, the major cause of CVD. NAFLD results from insulin resistance and it is considered as part of the metabolic syndrome. The interaction of hypertension, fatty liver and the metabolic syndrome is complex. More importantly, coexistence of liver fat accumulation and high blood pressure would potentiate the risk for cardiovascular disease... This study is a prospective study to assess the prevalence of NAFLD in hypertensive patients.In this study, NAFLD was present in 38% of the hypertensive patients. The prevalence of NAFLD was higher among the stage 2 hypertensives. it has been recognized that NAFLD represents an important burden of disease for patients with hypertension and is gaining importance. More importantly, coexistence of liver fat accumulation and high blood pressure would potentiate the risk for cardiovascular disease. Thus, it is important to identify NAFLD and hypertension and assess the initial risks of cardiovascular diseases